Literasi Pasar Modal dan Financial Freedom bagi Perangkat Desa Banyuwangi - Sandra Sukma Embuningtiyas; Izzato Millati (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
Financial literacy is a crucial foundation for improving financial well-being and achieving financial freedom. One aspect of financial literacy that has not yet been well-educated by the public is capital market literacy, which can be utilized as an investment alternative. Village officials are public servant, not all of whom have civil service status, and often face many difficulties in managing their finances. Therefore, knowledge and skills are needed to allocate their income more productively. This research is based on community service activities aimed at improving the financial literacy of village officials through an introduction to the capital market. The implementation method was carried out through socialization, training, and interactive discussions on understanding capital market mechanisms, recognizing types of investment instruments, understanding the benefits and risks of investment, and simple strategies for investing safely and sustainably. The results of the activity showed an increase in participants' knowledge and interest in utilizing capital market instruments as a means of long-term financial planning. This activity confirms that capital market literacy not only has the potential to help village officials achieve financial freedom but also encourages villagers to have a good understanding of investment and be competitive in today's modern era.